2020
DOI: 10.1017/jfm.2020.625
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic models for capturing dispersion in particle-laden flows

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Treating the hydrodynamic force as a stochastic variable offers some potential advantages over the classical BBO treatment of modeling each force contribution separately. Rather than attempting to tease out how each pair-wise neighbor interaction contributes to the hydrodynamic force on a given particle, Lattanzi et al (2020) demonstrated that the statistics obtained from treating the force as a stochastic variable are reconcilable with PR-DNS.…”
Section: Summary Pointsmentioning
confidence: 99%
“…Treating the hydrodynamic force as a stochastic variable offers some potential advantages over the classical BBO treatment of modeling each force contribution separately. Rather than attempting to tease out how each pair-wise neighbor interaction contributes to the hydrodynamic force on a given particle, Lattanzi et al (2020) demonstrated that the statistics obtained from treating the force as a stochastic variable are reconcilable with PR-DNS.…”
Section: Summary Pointsmentioning
confidence: 99%
“…The force Langevin (FL) theory examined by Lattanzi et al [19] is employed here to describe the neighbor-induced fluctuating drag force…”
Section: Force Langevin Frameworkmentioning
confidence: 99%
“…where τ F is the integral time scale of the fluctuating drag force, σ F is the standard deviation of the fluctuating drag force, and dW t is a Wiener process increment. We refer the interested reader to Lattanzi et al [19] where a detailed discussion regarding motivation for, and results from, the OU process are provided. Here, we briefly emphasize that the steady solution to the OU process is a normal distribution N [0, σ F ] and a multitude of PR-DNS studies have reported normally distributed drag forces 10,12,13,18].…”
Section: Force Langevin Frameworkmentioning
confidence: 99%
See 2 more Smart Citations